Distribuição espacial e determinação da depreciação quantitativa e qualitativa causada por Tetranychus ogmophallos (Acari: Tetranychidae) ao amendoinzeiro - Melville, Cirano Cruz [UNESP] (2015)
In recent growing seasons, there was a significant increase in the incidence of mite in peanut fields. Large infestations of pest mites affect the development and crop productivity, increases production costs, and contribute to increased environmental contamination due to intensive use of pesticides to control these arthropod. Field Information and observations indicate that the main pest mites that have caused damage to producers in São Paulo belong to Tetranychidae. This work aimed to study the type of spatial distribution of Tetranychus ogmophallos Ferreira e Flechtmann (Acari: Tetranychidae) mite on peanut, which probability distribution model that best represents your behavior in the field, as well as, determine the quantitative and qualitative depreciation caused by the mite to peanut crop. The experiments were carried out in the field and in a greenhouse belonging to the Faculty of Agricultural and Veterinary Sciences - UNESP/FCAV, Jaboticabal - SP. To determine the spatial distribution of the mite on peanut two fields with peanut were selected. In selected fields were examined plant materials consisting of leaves, leaflets and petioles, collected in the lower and top of the plant. The plants were spaced 22.5 m from one another. The first collect of samples of plant material was performed twenties days after planting, and the other every fifteen days. To determine the quantitative and qualitative depreciation experiments were conducted in a greenhouse, arranged in a completely randomized design consisting of two treatments, plants infested and non-infested (control), with 20 repetitions. The age of infestation varied in each experiment based on the number of days (15, 30, 60, and 90) after seedling emergence. Approximately 3,000 mites were transferred for each infestation. Data were submitted to analysis of variance, and means were compared by F test at 5% probability and the aggregation indexes were used to study the ...